Ekranisasi novel Argantara karya Falistiyana ke Film Argantara karya Guntur Soeharjanto - Arfithin, Ulfatri; Zulfadhli (Universitas Negeri Padang, 2024)
This study aims to describe the aspects of reduction, addition and variation changes that occur in the elements of plot, setting and characterization. The object of this research is the novel Argantara by Falistiyana published in 2021 and the movie Argantara directed by Guntur Soeharjanto in 2022. This research is a literary research using descriptive method. The data in this research is the entire text content of the novel and movie. The research instrument is the researcher himself. The data collection technique is to read the novel and watch the movie repeatedly then inventory it into the data inventory format and group the data related to the process of ekranisasid from the novel into the film. The data analysis technique used is grouping data about ekranisasi through the categories of aspects of reduction, addition and varied changes from the novel Argantara by Falistiyana into the film Argantara by director Guntur Soeharjanto, concluding the results and writing a report on the results of the analysis in the form of a thesis. The results of this research are: (1) there are 32 reductions in the plot element, 14 reductions in the setting element, and 25 reductions in the characterization element of the novel, (2) there are 41 additions in the plot element, 7 additions in the setting element and 3 additions in the characterization element of the movie, (3) there are 8 changes in the plot element, 4 changes in the setting element, and 6 changes in the characterization element of the novel. This ecranization process adapts the lives of generation z and the media in the process of changing it.